Implementation Of Hr Strategy On Employee Development, Involvement In Collaborative And Participatory Approach - Surya Kusumah; Dila Fitriani; Satriadi Satriadi (International Journal of Management Research and Economics, 2025)
This research discusses the implementation of HR strategies in employee development, employee involvement in collaborative and participatory approaches, while the purpose of this is to describe, explain, and know human resource development strategies, using some literature. This study used a qualitative research method with a descriptive approach. The results of observations and articles, journals, all of which were successfully collected and then analyzed. Which would like to see how the influence of HR strategy in employee development, because human resource employees are one of the crucial factors in human resource management. By involving employees to obtain long-term growth longevity and increase profitability in the midst of increasingly fierce industry competition. in a collaborative and participatory employee approach, meaning that the company involves employees effectively in the process of decision making, planning, and carrying out tasks. this approach also encourages employees to contribute, which empowers an inclusive work culture and actively participates in the development of organizational strategy implementation.